What is the solution of the equation  x/3−9=6  solving for x ? 

9 answers

To solve the equation \( \frac{x}{3} - 9 = 6 \) for \( x \), follow these steps:

  1. Add 9 to both sides to isolate the term involving \( x \): \[ \frac{x}{3} - 9 + 9 = 6 + 9 \] This simplifies to: \[ \frac{x}{3} = 15 \]

  2. Multiply both sides by 3 to solve for \( x \): \[ 3 \cdot \frac{x}{3} = 15 \cdot 3 \] This simplifies to: \[ x = 45 \]

Therefore, the solution is \( x = 45 \).

Randall needs to solve the equation  5x + 8 = 63 . His first mathematical operation used to isolate x is subtraction. Which value will he apply it to?

To isolate \( x \) in the equation \( 5x + 8 = 63 \) using subtraction, Randall should subtract 8 from both sides of the equation.

Here's how it looks:

  1. Original Equation: \[ 5x + 8 = 63 \]

  2. Subtract 8 from both sides: \[ 5x + 8 - 8 = 63 - 8 \]

This simplifies to: \[ 5x = 55 \]

So, the value Randall will apply the subtraction to is 8 (the constant term on the left side of the equation).

So what’s the answer

Randall will apply the subtraction to the value 8 in the equation \( 5x + 8 = 63 \).

Marion is solving the equation 9x − 6 = 12. As a first step, she adds 6 to both sides of the equation. In the next step, by what value does each side need to be divided

Let's start with Marion's equation:

\[ 9x - 6 = 12 \]

Her first step is to add 6 to both sides:

\[ 9x - 6 + 6 = 12 + 6 \]

This simplifies to:

\[ 9x = 18 \]

In the next step, to isolate \( x \), Marion needs to divide both sides by the coefficient of \( x \), which is 9.

So, each side needs to be divided by 9 in the next step.

The next step would look like this:

\[ \frac{9x}{9} = \frac{18}{9} \]

This simplifies to:

\[ x = 2 \]

Thus, the answer is 9.

Beejal is solving the equation  y/7 − 3 = 39 .(1 point)
As a first step, he starts by adding ______ to both sides of the equation, and then continues by multiplying by _______ on each side. 

Let's solve the equation step by step:

The given equation is:

\[ \frac{y}{7} - 3 = 39 \]

First Step: Adding to Both Sides

To isolate the term with \( y \), Beejal should first add 3 to both sides of the equation:

\[ \frac{y}{7} - 3 + 3 = 39 + 3 \]

This simplifies to:

\[ \frac{y}{7} = 42 \]

So, the value Beejal adds to both sides is 3.

Next Step: Multiplying Both Sides

In the next step, to isolate \( y \), he should multiply both sides by 7 (the denominator of the fraction):

\[ 7 \cdot \frac{y}{7} = 42 \cdot 7 \]

This simplifies to:

\[ y = 294 \]

Summary

  • Beejal starts by adding 3 to both sides of the equation.
  • He continues by multiplying both sides by 7.
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 7 answers
more similar questions